(6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)=

Simple and best practice solution for (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= equation:

Simplifying
(6x4y3 + 9x3y2) + (3x3y3 + -2x3y2 + -7xy) = 0

Reorder the terms:
(9x3y2 + 6x4y3) + (3x3y3 + -2x3y2 + -7xy) = 0

Remove parenthesis around (9x3y2 + 6x4y3)
9x3y2 + 6x4y3 + (3x3y3 + -2x3y2 + -7xy) = 0

Reorder the terms:
9x3y2 + 6x4y3 + (-7xy + -2x3y2 + 3x3y3) = 0

Remove parenthesis around (-7xy + -2x3y2 + 3x3y3)
9x3y2 + 6x4y3 + -7xy + -2x3y2 + 3x3y3 = 0

Reorder the terms:
-7xy + 9x3y2 + -2x3y2 + 3x3y3 + 6x4y3 = 0

Combine like terms: 9x3y2 + -2x3y2 = 7x3y2
-7xy + 7x3y2 + 3x3y3 + 6x4y3 = 0

Solving
-7xy + 7x3y2 + 3x3y3 + 6x4y3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'xy'.
xy(-7 + 7x2y + 3x2y2 + 6x3y2) = 0

Subproblem 1

Set the factor 'xy' equal to zero and attempt to solve: Simplifying xy = 0 Solving xy = 0 Move all terms containing x to the left, all other terms to the right. Simplifying xy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-7 + 7x2y + 3x2y2 + 6x3y2)' equal to zero and attempt to solve: Simplifying -7 + 7x2y + 3x2y2 + 6x3y2 = 0 Solving -7 + 7x2y + 3x2y2 + 6x3y2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.